Development of new methods to assess invertebrate immunology and immunotoxicology in aquaculture: oysters and lobsters as examples. (1st October 2008) - De Guise, Sylvain; Goedken, Michael; Morsey, Brenda; Maratea, Jennifer; Sidor, Inga; Perkins, Christopher
In order to support healthy aquaculture, we developed assays to assess immune functions and their susceptibility to environmental conditions or toxicants. Flow cytometry allowed the rapid and quantitative analysis of oyster and lobster cell subpopulations and their functions (phagocytosis, peroxide production, natural killer cell-like activity and apoptosis). We demonstrated experimentally that water salinity, water temperature and infection with P. marinus modulated oyster defence mechanisms, and lobsters relative sensitivity to the effects of pesticides. This information will improve the understanding of resistance to pathogens as well as the potential effects of environmental changes to affect disease resistance.